2017
DOI: 10.21873/anticanres.11786
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity Induced by Dental Materials: A Comprehensive Review

Abstract: Abstract. Genotoxicity is the capacity of an agent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 91 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…Assessment of genotoxicity of dental materials is essential for determining the health dangers due to an evidenced link between genetic damage and carcinogenesis. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Assessment of genotoxicity of dental materials is essential for determining the health dangers due to an evidenced link between genetic damage and carcinogenesis. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Actually, a recently published review regarding genotoxicity induced by dental materials does not include any of the materials evaluated in our study. 9 Despite this, the behavior of light-cure dressing materials evaluated in this study can be explained by analyzing the genotoxicity of their individual components, specially the urethane dimethacrylate monomer, where a study found that this compound did not induce strand breaks in an isolated plasmid DNA. 30 This study also evaluated the ultimate tensile strength of periodontal dressing materials.…”
Section: Discussionmentioning
confidence: 93%
“…These tests are commonly used for the initial assessment of the toxic effects of dental materials, presiding the pre-clinical and clinical evaluation. 8,9,10 One important factor for the delineation of in vitro cytotoxic test is the choice of an adequate cell line related with the intended application of the material. 11,12 In this study, periodontal dressings were tested against fibroblasts, since connective tissue is the most frequently protected tissue by surgical dressings in periodontal surgeries and to follow recommendations from the ISO 10993-5.…”
Section: Discussionmentioning
confidence: 99%
“…However, a certain degree of toxicity ranging from a mild allergic response to genotoxicity and mutagenicity is observed in a plethora of dental materials, including sodium hypochlorite. [ 5 ] Recently, an organic carcinogen named 2,6-xylidine was reported by Vidhya et al . formed on the interaction between lidocaine hydrochloride and sodium hypochlorite.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of any carcinogen in the root canal system over a longer duration under constant function will lead to its eventual seepage into the periapical environment. [ 5 ] Saravanakarthikeyan et al . conducted a study, which showed the persistence of this precipitate in the canal even after chemo-mechanical preparation.…”
Section: Introductionmentioning
confidence: 99%